Role of depression in development of functional dyspepsia symptoms - D. B. Kolesnikov; S. I. Rapoport; L. A. Voznesenskaya; M. I. Rasulov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To reveal a role of a psychological distress, in particular depressive disorders, in development of symptoms of functional dyspepsia.Material and methods. Overall 53 patients with complaints of pain, burning, nausea, eructation, flatulence, early satiety, heaviness and distension in epigastrium were investigated. For verification of the «functional dyspepsia» diagnosis all patients were divided into two groups according to results of esophagogastroduodenoscopy. The first group included 18 patients at whom presence of dyspeptic complaints conformed the endoscopic pattern (erosive esophagitis, erosive gastroduodenitis). This group has been excluded from the further study. The second group (35 patients) has been represented by patients with functional dyspepsia at whom clinical symptoms could not be completely explained by the revealed organic changes of gastro-intestinal tract (GIT) – lower esophageal sphincter incompetence, atrophic and superficial gastritis.Results. Psychopathologic and psycho-diagnostic investigations have shown, that at all patients with functional dyspepsia symptoms of anxiety and depressive disorder have been revealed. Thus moderate depression was detected in 20 (57,1%) patients, severe depression – in 15 patients (42,9%). The level of anxiety by Spielberger scale in 11 patients was in the range of 31–45 points that indicates moderate degree of anxiety, while in 9 patients the anxiety reached severe degree (>46 points).Conclusions. Obtained data allow to judge quite convincingly that at patients with functional dyspepsia the symptom-complex of disorders related to GIT develops due to clinical manifestations of depression and anxiety.